Hydrogen effect on half‐metallic and thermoelectric properties of CoRhMnSi [001] film. (26th March 2021) - Sherzad Othman, Mazin; Sadeghi, Mohammad; Vahabzadeh, Nosrat‐Ali; Boochani, Arash; Amiri, Maliheh
Summary: Quaternary Heusler alloys (QHAs) with their unique properties have the ability to absorb and store hydrogen to be used as hydrogen storage sources. In the present work, based on the calculations of the density theory of the effects of hydrogen adsorption on the properties of the half‐metal and the electron transport behavior of the thin film CoRhMnSi alloy [001] was investigated. CoRhMnSi is a ferromagnetic half‐metallic compound that crystallizes in a LiMgPdSn‐type cube structure and only its two phases [001] named β and γ under hydrogen adsorption still retain their metallic properties with band gaps of 0.81 and 0.39 eV in the minor spin, have maintained. Examination of thermodynamic phase diagrams shows that these films are stable in thermodynamic conditions. Investigation of thermoelectric properties of these compounds also shows that the highest figure of merit values of 0.99 for the CoRhMnSi bulk and 0.81 for the γ phase occurs in the room temperature range. Abstract : Hydrogen adsorption and storage is one of the fields of interest for studies, so based on DFT calculations, we studied the effects of hydrogen adsorption on the electronic and thermoelectric behavior of CoRhMnSi [100] films. These films under hydrogen adsorption show good half‐metallic ferromagnetic properties and good thermoelectric performance.